Virtuelles Museum: Antinoos Portraits (2009)
[Dt.:] Die Seite ist vorrangig wissenschaftlich brauchbar aufgrund ihrer Bildergalerie zu Porträts des Antinoos, der historischen Figur des Geliebten Kaiser Hadrians', der als Zwanzigjähriger im Nil ertrunken ist. - [Engl.:] This homepage focuses on different pictures of Antinous portraits (a historical figure, who was the lover of emperor Hadrian and who was drowned while bathing in the river Nile).